Markov Chain and Cluster Model of Green Algae Phytoplankton (Chlorophyceae) Diversity and Spatial Distribution Pattern along Stream, Water Quality, and Land Use Gradients in Krukut River, Jakarta City - Andriwibowo Andriwibowo; Adi Basukriadi; Erwin Nurdin; Amanda Zahra Djuanda; Elizabeth Adeline; Zeadora Abbya Trisya (School of Life Sciences and Technology, Institut Teknologi Bandung, 2022)
Green algae phytoplankton (Chlorophyceae) have a wide aquatic distribution, including saltwater and freshwater environments. Compared to the ones living in saltwater, green algae diversity in freshwater ecosystems in rivers is influenced by stream gradients, water quality, and land uses. Meanwhile, in Jakarta, 17 rivers have the potential to provide a habitat for green algae communities. Due to anthropogenic activities, river streams have been affected by influences that may affect the water quality and green algae community along stream gradients. One of the critical rivers in Jakarta is the Krukut river, which has the most extended stream spanning over 40 km and downstream in Jakarta bay. This study aims to model the diversity and distribution pattern of green algae in the Krukut river from its upstream segment in Jakarta city, surrounded by settlements, to the downstream segments in Jakarta bay. The distribution model uses the Cluster Analysis and Markov Chain Model to elaborate the probabilities of green algae phytoplankton distribution in downstream, midstream, and upstream segments of the Krukut river. The results show that 7 species of Chlorophyceae have been recorded in the Krukut river. All species had a high likelihood of being found downstream, particularly Cosmarium sp., Eudorina sp., Spyrogyra sp., and Volvox sp. Regarding distribution, all phytoplankton species have a high probability (4%–31%) and tendency to be distributed from upstream and midstream to downstream rather than from downstream to midstream and upstream, with probability ranges of 2%–27%. The probability and tendency of phytoplankton distribution towards downstream directions avoiding upstream were related to the deteriorating water quality in the upstream, characterized by high turbidity, low dissolved oxygen, and more acidic water.